AN EVALUATION OF THE UK FOOD STANDARDS AGENCY'S SALT CAMPAIGN. (6th January 2012) - Shankar, Bhavani; Brambila‐Macias, Jose; Traill, Bruce; Mazzocchi, Mario; Capacci, Sara
ABSTRACT: Excessive salt intake is linked to cardiovascular disease and several other health problems around the world. The UK Food Standards Agency initiated a campaign at the end of 2004 to reduce salt intake in the population. There is disagreement over whether the campaign was effective in curbing salt intake or not. We provide fresh evidence on the impact of the campaign, by using data on spot urinary sodium readings and socio‐demographic variables from the Health Survey for England over 2003–2007 and combining it with food price information from the Expenditure and Food Survey. Aggregating the data into a pseudo‐panel, we estimate fixed effects models to examine the trend in salt intake over the period and to deduce the heterogeneous effects of the policy on the intake of socio‐demographic groups. Our results are consistent with a previous hypothesis that the campaign reduced salt intakes by approximately 10%. The impact is shown to be stronger among women than among men. Older cohorts of men show a larger response to the salt campaign compared to younger cohorts, while among women, younger cohorts respond more strongly than older cohorts. Copyright © 2012 John Wiley & Sons, Ltd.